Jelovo-bukovi gozdovi v dolini Loške Koritnice v Julijskih Alpah (severozahodna Slovenija) - Dakskobler, Igor (Gozdarski vestnik, 2004)
Applying the standard Central-European method (BRAUN-BLANQUET 1964) we carriedout a phytosociological study of forest stands of beech, fir, spruce and larch which thrive on the very steep shady dolomite slopes of the Loška stena rock walls above the Koritnica valley in the Julian Alps. After comparing their floristic composition with similar stands elsewhere in the region of the South-eastern Alps and in the northern part of the Dinaric mountains (DAKSKOBLER 2002a, b, c) we classified them into the syntaxon Homogyno sylvestris-Fagetum Marinček et al. 1993 var. geogr. Luzula nivea Marinček ex Dakskobler 2002 rhododendretosum hirsuti Dakskobler 2002 var. Homogyne alpina var. nov. The differential species of the new variant are Vaccinium vitis-idaea, Homogyne alpina, Sorbus chamaemespilus, Lycopodium annotinum and Pinus mugo. The fir-beech stands described are among the most natural forest stands in the Soča Valley and have been least disturbed by human impact, so it would be sensible in the future to study their structure and dynamics in more detail.
Keywords: fitocenologija; gozdovi; jelovo-bukovi gozdovi; Julijske Alpe; Log pod Mangartom; Slovenija